(3GdOahY aj GdTjcs - (3TQja(B, (3GdWHGNs ([(3O(B.(3e(B.]:s [(3O(B.(3f(B.],s, 2002)
(3JYQja GdTjc hCMcGe bGfhf GdTjc GdLOjO, TQhW UMI GdTjc, LQGFe GdTjc, GdOahY GdeJYdbI HGdTjcs
Keywords: (3GdTjcGJs; (3GdbGfhfs; (3LQGFe GdCehGds